Butterfly dispersal and longevity in unlogged and selectively logged forest - Suzan Benedick; J. K. Hill; Keith C. Hamer; Nazirah Mustaffa; Chey, V. K.; Maryati Mohamed (Forest Research Centre, Sabah Forestry Department, 2007)
This study investigated butterfly dispersal and longevity in unlogged and selectively logged forest in lowland dipterocarp rainforest Sabah, Malaysia (Borneo). Fruit-baited traps were used to survey butterflies in unlogged forest and forest that had been selectively logged 10-12 years previously in 1988 and 1989. The study focused on butterflies in the subfamilies Satyrinae, Nymphalinae, Morphinae and Charaxinae of the family Nymphalidae. Traps were set up along four transects on existing paths and trails in unlogged forest (two transects, total length 4 km) and logged forest (two transects, total length 4 km). Traps were hung 1-2 m from the ground at 100 m intervals along transects (total of 80 traps). Traps were operated for 12 days each month (October 1999-September 2000). Dispersal and longevity were investigated in several of the more abundant species. Dispersal and longevity were investigated in seevral of the more abundant species. Dispersal and longevity were investigated in several of the more abundant species. Dispersal and longevity did not differ between habitats or sexes but did differ between species in relation to body size and subfamily. The maximum distance moved by an individual in this study was 4670m and the maximum lifespan was 175 days (Bassarona dunya in both cases).